As formas do mito nos cantares amazônicos do poeta João de Jesus Paes Loureiro - SILVA, Nivaldo Carlos Lima da (Universidade Federal do Pará, 2011)
It analyses the poems from Amazon Trilogy objectifying to point out how the poet relives and recreates a little bit about the History of Amazon. Concepts theorical-methodologies from own poet like semiotic conversion, negative epiphany and others beyond to use works which retract the situation of Amazon region since 1950, period of implantation of development project to modernization itself. Poems will be read at light from this cultural e historic context which the new capitals arrived to region breaking the relationship in this place. How it was the process? And which the consequences to the primitive populations and to nature which to change in paradox space of civilization and barbarian, product of exploration and greed, perturb the Amazon man? How process itself the passage from a mythical thought to a rationally, so the mythical deslegend and the vision of city like space of ruin: memory and forgetfulness and also of vices in this route between poetry and reality is that realize who poet to gather from his context the raw material to the poetry changing the reality like aesthetics material, isn’t to aesthetic the misery , but how way to give poetical form to historical time that cross and it is crossed like myth, or poetical forms of myth.